(untitled) (Bangladesh Journal of Urology, 2020)
Objective: T0 compare the outcome of Transurethral Resecton of Prostate between Patients with Preoperative Low or Normal and High Voiding Pressure. Methods: This hospital based prospective observational study was conducted in the Department of Urology of Dhaka Medical college Hospital from July 2008 to June 2010 on male patients aging >59 years having Lower urinary tract symptoms (LUTS) attending to urology OPD& IPD were evaluated by history, physical examination including DRE and necessary investigations like USG of KUB and prostate with MCC & PVR, Q max, IPSS score to identify the potential candidates for TURP. Potential participants were counseled for urodynamic study. Who fulfilled the selection criteria included in this study in outpatient basis or admitted in the urology ward and numbered chronologically and performed urodynamic study and then patients underwent TURP, after 12 weeks of completion of TURP again a follow-up urodynamic study performed in all patients to compare the outcome between two groups. Sample size was 65, high pressure voiding group were 36 in number and Normal or low pressure voiding group were 29 in number. Data were collected on variables of interest using a structural data collection format. Data were processed and analyzed using SPSS (Statistical package for social science) software program. The test of significant employed to analyze the data was descriptive statistics and Student’s t-test, Paired and unpaired t- test, Fisher exact test. Probability value (P value < 0.05) was considered significant. Results: In this study the age ranges were 59 and 88 years and mean age was 70.7 ± 6.7 years. the maximum urinary flow rate, residual urine volume and maximum intravesical pressure 3 months after transurethral prostatic resection were significantly better in patients with high detrusor pressure compared to those with normal/low normal/low detrusor pressure (15.9±0.7 vs. 21.3±2.2ml/sec, p<0.001, 18.1±11.8 vs. 2.9±0.7 ml, p<0.001 and 48.3±6.2 vs. 71.9±15.2 cmH2O, p<0.001 respectively).The maximum urinary flow rate ( Q max ), residual urine volume, maximum intravesical pressure and detrusor pressure at peak urinary flow rate and also IPSS score were significantly improved 3 months after operation in both groups, more improvement was observed in preoperative high voiding pressure group. Post-voiding residual urine is a clear indication of poor outcome, and also the maximum urinary flow rate, maximum intravesical pressure and detrusor pressure at peak urinary flow rate all factors may precipitate decompensation of bladder and in low voiding pressure group decompensation of bladder occurs more than the high voiding pressure group as the preoperative and postoperative residual urine develops more in low voiding pressure group. Conclusion: The high voiding pressures (detrusor pressure) may influence in good postoperative outcome and helps in resolution of a significant outflow obstruction, there are good urodynamic reasons for avoiding unwanted TURP rather it could be justified by using urodynamic study which may predict outcome of TURP. So, we may assess properly the patient for prostatectomy by urodynamic study. As if we do this type of evaluation before TURP it may reduce the unwanted operation. Bangladesh Journal of Urology, Vol. 21, No. 2, July 2018 p 111-119